2013
DOI: 10.1158/1940-6207.capr-12-0385
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Changes in Diet and Physical Activity in Breast and Colorectal Cancer Screening Settings: An Unexplored Opportunity for Endorsing Healthy Behaviors

Abstract: The importance of diet, physical activity, and weight management in breast and colorectal cancer prevention is widely recognized. While there may be many "teachable moments" that could be used to assess and initiate changes in these behaviors by health professionals (to complement public health campaigns), there is little evidence that lifestyle is discussed within cancer screening settings. The lack of advocacy about lifestyle in these settings may endorse poor health behaviors, in particular the absence of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 25 publications
2
49
0
Order By: Relevance
“…For many patients, experiencing a cancer diagnosis represents a teachable moment that can inform their future behaviors, and many are eager to make adjustments to diet, exercise, and tobacco use because these represent behaviors within their control that can potentially lower their risk of developing future cancers. 37-39 Existing studies have shown that, for these reasons, provider recommendations during survivorship care may be more likely to have an impact on improving preventive behaviors. 37-39 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For many patients, experiencing a cancer diagnosis represents a teachable moment that can inform their future behaviors, and many are eager to make adjustments to diet, exercise, and tobacco use because these represent behaviors within their control that can potentially lower their risk of developing future cancers. 37-39 Existing studies have shown that, for these reasons, provider recommendations during survivorship care may be more likely to have an impact on improving preventive behaviors. 37-39 …”
Section: Discussionmentioning
confidence: 99%
“…37-39 Existing studies have shown that, for these reasons, provider recommendations during survivorship care may be more likely to have an impact on improving preventive behaviors. 37-39 …”
Section: Discussionmentioning
confidence: 99%
“…Cognitive screening instruments are non‐invasive, do not require physical burdens, and not require any special facilities and expensive equipment. Furthermore, undergoing screening provides a good opportunity to encourage these health behaviors . Thus, promoting participation in screening for cognitive impairment and detecting cognitive impairment at an earlier stage is important for preventing an increase of dementia.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, large population-based studies have shown that even small changes in lifestyle (although insignificant on an individual level) can affect mortality on a population level 7 8. Although the effect of screening on lifestyle changes is currently unknown, lifestyle counselling in conjunction with attendance to cancer screening programmes has been proposed 9 10. Thus, it is important to investigate long-term effects of cancer screening on lifestyle on the population level.…”
Section: Introductionmentioning
confidence: 99%